Characterization of monoethanolamine + potassium lysinate blend solution as a new chemical absorbent for CO2 capture. (August 2016) - Ramazani, Roozbeh; Samsami, Aria; Jahanmiri, Abdolhossein; Bruggen, Bart Van der; Mazinani, Saeed
Highlights: PL was examined as a potential promoter of MEA solutions in CO2 loading capacity. New solubility data for CO2 loading capacity in solutions of PL + MEA was reported. PL + MEA was proposed as a new chemical absorbent for CO2 capture. Furthermore, new experimental values of densities, viscosities and corrosion rates of the used solutions were reported. CO2 loading capacity of PL + MEA is higher than pure MEA. Abstract: Selection of an appropriate absorbent can provide a potential breakthrough for the chemical absorption method. In this study, after a prescreening, potassium lysinate (PL), an amino acid with high loading capacity, has been selected to blend with monoethanolamine (MEA), an industrial absorbent with high reaction rate, to improve the performance of MEA for CO2 removal. To evaluate the effect of the addition of PL to MEA in terms of loading capacity, the equilibrium solubility of CO2 in MEA + PL blend solutions was determined experimentally by using a Vapor-Liquid Equilibrium (VLE) at total blend concentration (CT ) 2.5 mol/L in temperatures between 303 and 323 K and CO2 partial pressure ranging from 0 to 50 kPa. For further investigation, the density, viscosity (from 303 to 323 K) and corrosion rate (at 313 K) of blend solutions were also determined. The obtained results indicated that the loading capacity and corrosion rate of blend solutions increase as the blend ratio of PL/MEA increases while viscosity decreases.